Loss of endothelial TRPC1 aggravates metabolic dysfunction in obesity via disrupting adipose tissue homeostasis - Lan, Yihui; Wang, Shiquan; Chu, Yuan; Zhang, Yizhi; Liu, Yuan; Yu, Fan; Feng, Lei; Zhu, Yifei (Frontiers in Molecular Biosciences, 2025)
IntroductionWhile obesity exacerbates metabolic disorders through vascular endothelial dysfunction, the specific regulatory mechanisms of endothelial cells underlying this process remain poorly defined. Although the transient receptor potential canonical 1 (TRPC1) channel demonstrates tissue-specific heterogeneity in metabolic regulation, its functional role within endothelial cells and its contribution to metabolic disturbances associated with obesity remain unresolved.MethodsWe established endothelial-specific TRPC1 knockout (TRPC1EC−/−) and overexpression (TRPC1ECKI/KI) mouse models, which were integrated with a high-fat diet (HFD)-induced obesity paradigm. Through comprehensive metabolic phenotyping, adipose tissue molecular profiling, and serum metabolomics analysis, we systematically dissected the regulatory mechanisms of endothelial TRPC1 in glucose and lipid metabolism.ResultsEndothelial TRPC1 deficiency, while not altering the severity of HFD-induced obesity, significantly exacerbates impaired glucose tolerance, insulin resistance, and dyslipidemia. Mechanistically, the deficiency of endothelial TRPC1 enhances the expression of chemokines (CCL3/CXCL5) and pro-inflammatory cytokines (IL-1β/TIMP1), thereby creating an inflammatory microenvironment in epididymal white adipose tissue (eWAT) and suppressing PGC1α/UCP1-mediated thermogenic function. Metabolomic profiling further reveals that TRPC1 deficiency drives systemic metabolic perturbations, including the depletion of serum 1-methylhistidine and N-acetylvaline, alongside the aberrant accumulation of gibberellin A12, which suggests disrupted amino acid metabolism and the activation of non-canonical inflammatory pathways. Conversely, endothelial TRPC1 overexpression significantly ameliorates obesity-associated metabolic dysfunction, as evidenced by reduced visceral fat deposition, enhanced insulin sensitivity, and restored thermogenic capacity in adipose tissue.ConclusionThis study, for the first time, elucidates the pivotal role of endothelial TRPC1 in maintaining metabolic homeostasis by orchestrating an “inflammation-thermogenesis-metabolite” regulatory network. Specifically, the deficiency of endothelial TRPC1 exacerbates metabolic dysfunction associated with obesity, whereas its overexpression exerts significant protective effects. These findings highlight the centrality of endothelial ion channels in vascular-metabolic coupling, thereby establishing a theoretical rationale for targeting TRPC1 as a therapeutic strategy against metabolic syndrome.